Penerapan Penilaian Autentik Untuk Meningkatkan Perkembangan Anak Usia Dini - winta windira; Novita Loka (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Early childhood education (ECE) plays a crucial role in the holistic development of children, encompassing cognitive, social, emotional, and physical aspects. This study aims to explore the implementation of authentic assessment to enhance the development of early childhood at RA Al-Furqon. The method used is qualitative descriptive, with data collection through observation, interviews, and documentation. The results show that authentic assessment improves children's social skills, creativity, and cognitive abilities. Additionally, this assessment also boosts children's motivation and confidence in learning. However, challenges such as time constraints and the need for teacher training must be addressed to maximize the effectiveness of this assessment. This research is expected to contribute to designing assessment systems that better align with the developmental characteristics of young children.